PENGARUH KOMUNIKASI PERSUASIF INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN DI TIKTOK SHOP - Sa'adah, Salsabila Nur; Alfiyah, Rohmi; Hidayah, Nur; Zikrinawati, Khairani; Fahmy, Zulfa (Investama : Jurnal Ekonomi dan Bisnis, 2023)
TikTok is a social media and music video platform that creates a new feature called TikTok Shop as a means to make it easier for brands to attract consumer interest by carrying out attractive and practical marketing through social media. This study aims to determine the effect of influencers' persuasive communication on consumer purchasing decisions at the TikTok Shop. This study uses two research variables, namely persuasive influencer communication and purchasing decisions. Processing techniques and data analysis in this study used the normality test, linearity test as an assumption test, then tested the hypothesis using a simple linear regression test with the help of SPSS software. This research was conducted by distributing questionnaires to 200 TikTok Shop users. The results of the study show that influencers' persuasive communication has a significant influence on consumer purchasing decisions at the TikTok Shop.